The cardiac response to exercise in cirrhosis. Issue 2 (1st August 2001) - Wong, F; Girgrah, N; Graba, J; Allidina, Y; Liu, P; Blendis, L
Abstract : BACKGROUND: Impaired exercise capacity and oxygen consumption are common in cirrhosis. AIM: To explore the relationship between possible myocardial dysfunction and exercise tolerance in cirrhosis. METHODS: Cardiac responses to exercise, using radionuclide angiography and graded upright cycle ergometry with oxygen consumption, were assessed before and after exercise in 39 cirrhotics patients and compared with 12 age and sex matched healthy volunteers. Baseline cardiac chamber dimensions and wall thickness, ejection fraction, and diastolic function were measured using two dimensional echocardiography is all subjects. RESULTS: Baseline diastolic dysfunction with prolonged isovolumic relaxation times (p=0.02), left atrial enlargement, and left ventricular wall thickening were present in all cirrhotics (p=0.02), despite increased mean ejection fraction. With graded exercise, cirrhotics achieved 71 (4)% (p=0.03) (pre-ascitics) and 46 (3)% (p<0.001) (ascitics) of predicted work loads, respectively, without significant increases in ejection fraction. The smaller absolute and percentage increases in cardiac output (p=0.003) in the cirrhotics were associated with significantly reduced oxygen consumption (p=0.003) and anaerobic threshold (p<0.001), and correlated significantly with work and metabolic parameters. CONCLUSIONS: Impaired exercise capacity in cirrhosis is associated with myocardial thickening and ventricular stiffness leading to decreased diastolic function, inotropic and chronotropic incompetence under conditions of stress, with metabolic consequences. This picture is compatible with the condition now known as cirrhotic cardiomyopathy.